PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PPKn SISWA SMA ISLAMIYAH PONTIANAK - Nadiah, Nadiah; Sulistyarini, Sulistyarini; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of STAD type cooperative learning model (Student Teams Achievement Division) on PPKn learning outcomes in class X Pontianak Islamic High School. This research is an experimental study using the Posttest-Only Control Design research design. The independent variable of this study is the STAD type cooperative model while the dependent variable is learning outcomes. The subject of this study was the tenth graders of Pontianak Islamic High School divided into two classes, namely control class and experimental class. Data collection techniques used are tests and observations. The analysis needed includes validity test, difficulty level, different power index, reality test, normality test, homogeneity test and hypothesis test with a significance level of 5%. In the calculation process using the help of a computer program SPSS version 18.0 for windows. The results showed that there was an effect of STAD type cooperative learning model on student learning outcomes in PPKn X IPS class subjects at Islamic Islamiyah High School Pontianak, namely by using t test showing t value of 7.276 with a significance level of 0.000 or in other words 0.000 5 0.05 so Ho is rejectedKeywords: STAD type cooperative learning model, learning outcomes, Civics